2018
DOI: 10.3390/app9010005
|View full text |Cite
|
Sign up to set email alerts
|

Process Design of the Antioxidant Shuidouchi and Its Effect on Preventing Dextran Sulfate Sodium (DSS)-Induced Colitis in Mice via Antioxidant Activity

Abstract: Shuidouchi is a traditionally fermented soybean product in China. Shuidouchi production requires a variety of processes; however, the production process has not been standardized. It can be developed into high-quality products with enhanced health effects by improving the design of its fermentation process and increasing the content of its active ingredients. In this study, a single-factor experiment was conducted that established different process conditions to determine the fermentation conditions that achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…The colon length and colon weight/length ratio were among the criteria for assessing the severity of UC. The colon length of DSS‐induced UC mice was shorter than that of control mice, and the colon weight/length ratio of UC mice was decreased compared to normal mice (Zhang, Chen et al., 2019; Zhang, Li et al, 2019). These results indicated that LP‐YS3 could improve colitis.…”
Section: Discussionmentioning
confidence: 99%
“…The colon length and colon weight/length ratio were among the criteria for assessing the severity of UC. The colon length of DSS‐induced UC mice was shorter than that of control mice, and the colon weight/length ratio of UC mice was decreased compared to normal mice (Zhang, Chen et al., 2019; Zhang, Li et al, 2019). These results indicated that LP‐YS3 could improve colitis.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,6 UC can be treated by regulating intestinal flora and increasing the number of probiotic. [7][8][9] Therefore, increasing attention was paid to the potential and beneficial roles of probiotics in the control and regulation of IBD. Meta-analyses and systematic review reports showed that probiotics were beneficial to the treatment of IBD, especially the combined use of probiotics in treating UC.…”
Section: Introductionmentioning
confidence: 99%
“…The aggregation of neutrophils began to decline after intestinal inflammation, and a large amount of them entered into the circulation and migrated to tissues. At the same time, free radicals, such as reactive oxygen species and reactive nitrogen species, gathered in large quantities, which in turn led to damage and toxicity of colon tissue, and further aggravated colitis [ 21 ]. After colitis, the levels of SOD and GSH were reduced in colon tissue, while those of MDA and MPO were elevated.…”
Section: Discussionmentioning
confidence: 99%